Pengaruh Good Corporate Governance terhadap Internal Fraud pada Unit Usaha Syariah Tahun 2017 - Ayu Irmasari Raharjanti (Academica: Journal of Multidisciplinary Studies, 2018)
The fraud case has penetrated the world of Sharia banking, both Bank Umum Syariah (BUS) and Unit Usaha Syariah (UUS). Fraud involving banking companies, in the Good Corporate Governance (GCG) report, the bank only published the number of cases released> 100 million. This study uses 10 of the 20 UUS registered with the Financial Services Authority, the sample was obtained based on purposive sampling by looking at the publication of GCG reports on the banking site. Using the GCG self-assessment values processed by the simple SPSS 23 linear regression formula, it was found that Good Corporate Governance was not obtained against the Internal Fraud Unit of the Sharia Business.Keywords: Good Corporate Governance, Internal Fraud, Islamic, Finansial Institution.